Discourse network analysis of broadcasting policy in Indonesia: Case of ASO 2 November 2022 - Abyzan Syahadin Bagja Dahana; Rahayu Rahayu (Jurnal ASPIKOM - Jurnal Ilmu Komunikasi, 2025)
This study aims to identify actors, dominant discourses, and discourse coalitions in the debate surrounding the implementation of analog switch-off (ASO) in Indonesia on November 2, 2022 until the implementation of total ASO on August 17, 2023. This study employs discourse network analysis method with data sources in the form of 283 articles from 12 national online news outlets. The Ministry of Communication and Information Technology (Kominfo) became the most dominant actor, followed by the Indonesian House of Representatives (DPR RI), West Java citizens, Central Java citizens, and East Java citizens. The dominant discourses centered on criticisms of set-top box (STB) distribution performance; the perceived benefits of digitalization for the public; critiques of ASO implementation that overlooked citizen and stakeholder readiness; and repeated calls for intensified government socialization efforts. The debate produced six discourse coalitions–two supporting ASO and four criticizing it. While these coalitions revealed clear alignments and contestations, their influence remained limited, shaping only the level of discourse structuration rather than affecting policy outcomes